Understanding reader navigation patterns in multi-path hypertext fiction: a case study approach to Patchwork Girl - Nurul Hijja Mazlan; Candra Rahma Wijaya Putra; Hary Sulistyo (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: The rise of hypertext fiction has transformed narrative structures, challenging traditional reading behaviors and comprehension strategies. Objective:  This study aims to investigate how readers navigate and engage with Patchwork Girl, a seminal work in hypertext fiction, focusing on navigation patterns, motivations, and their impact on comprehension and engagement. Method: Employing a qualitative case study approach, the research involved 110 undergraduate English majors, using observations, interviews, and thematic analysis to uncover patterns and insights. Results: Findings revealed three dominant navigation strategies—linear, exploratory, and random—each influenced by motivations such as curiosity, thematic alignment, and a desire for agency. Implication: Linear navigation resulted in higher comprehension, while exploratory navigation fostered moderate engagement, and random navigation led to cognitive overload and fragmented understanding. Novelty: These findings underscore the importance of balancing narrative complexity with user guidance in hypertext design, offering valuable implications for digital storytelling and educational applications.